2017
DOI: 10.1155/2017/4028602
|View full text |Cite
|
Sign up to set email alerts
|

Establishing an Improved Kane Dynamic Model for the 7-DOF Reconfigurable Modular Robot

Abstract: We propose an improved Kane dynamic model theory for the 7-DOF modular robot in this paper, and the model precision is improved by the improved function T′it. We designed three types of progressive modular joints for reconfigurable modular robot that can be used in industrial robot, space robot, and special robot. The Kane dynamic model and the solid dynamic model are established, respectively, for the 7-DOF modular robot. After that, the experimental results are obtained from the simulation experiment of typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to the data of Table 4, it was found that the fitting result was better when j was equal to 5. en, the undetermined coefficient matrix P ij under the task is expressed by equation (23). e matrix is 0 to 5 powerrelated from the bottom to top:…”
Section: Improved Dynamic Model Analysis and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the data of Table 4, it was found that the fitting result was better when j was equal to 5. en, the undetermined coefficient matrix P ij under the task is expressed by equation (23). e matrix is 0 to 5 powerrelated from the bottom to top:…”
Section: Improved Dynamic Model Analysis and Modelingmentioning
confidence: 99%
“…According to equations (22) and (23), the correction function of the dynamic model at each joint is shown in equation (24). It is shown in equation (25) that the total expressions of the correction function are from joint 1 to joint 6.…”
Section: Improved Dynamic Model Analysis and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The principle of virtual work establishes dynamic equation based on that sum of virtual work done by active force and moment, inertia force and moment are equal to zero [6]. Kane equation method solves the unknown quantity by means of the equilibrium equation about the generalized velocity, partial velocity, active force and inertial force of the rigid body [7]. When carrying out deformation coordination analysis, it is necessary to calculate the forces between components at the spherical joint.…”
Section: Introductionmentioning
confidence: 99%
“…Lagrange method is based on the energy of the system and uses the kinetic energy and potential energy of the system to establish the energy function [9]. Kane equation is derived from the general dynamic equation and is applicable to both nonholonomic and complete systems [10]. Newton-Euler equation decomposes the motion of a rigid body into translation and rotation, which are described by Newton's law and Euler equation respectively [11,12].…”
Section: Introductionmentioning
confidence: 99%